Management of chronic ocular sarcoidosis: challenges and solutions - Matsou A (Dove Medical Press, 2018)
Artemis Matsou,1 Konstantinos T Tsaousis2 1Second Department of Ophthalmology, Papageorgiou General Hospital, Aristotle University of Thessaloniki, Greece; 2Ophthalmology Department, Leicester Royal Infirmary, University Hospitals of Leicester, Leicester, UK Background: Sarcoidosis constitutes one of the leading causes of ocular inflammation. Chronic ocular sarcoidosis can affect any segment of the eye and its adnexa, producing a wide range of clinical manifestations and severity. If left untreated, permanent visual impairment or even blindness may ensue. Treatment approaches vary from topical therapy to systemic agents that induce immunosuppression to different levels according to disease severity. Objective: To review the published literature on the management options for chronic ocular sarcoidosis and provide a comprehensive list of available treatment strategies, including the newer biologics. Summary: Ocular disease remains a challenging aspect of sarcoidosis and may even be the presenting sign of the disease. Prompt and effective therapy may reverse visual damage and prevent permanent loss of vision. Because of the complexity of the disease, a multidisciplinary approach is often required, with a view to addressing both the ocular and other systemic manifestations of sarcoidosis. Recent data suggest that achieving overall optimal systemic control is of paramount importance in controlling eye inflammation as well. Cytotoxic immunosuppressive agents for refractory chronic ocular disease, as well as biologic anti-TNFα therapies, have advanced the management of chronic disease and should be considered corticosteroid-sparing strategies before the onset of significant steroid-induced morbidity. Keywords: ocular sarcoidosis, uveitis, immunosuppression, biologic agents, anti-TNFα